THE NGALU KEMENAKAN TRADITION IN THE FORM OF SOLIDARITY VALUES IN THE COMMUNITY OF KOTO DIAN VILLAGE HAMPARAN RAWANG DISTRICT - Yolla Ramadani; Hafizah . (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
The Ngalu Kemenakan tradition is a tradition that is carried out on the first child of a male tuo child. This tradition is carried out with several processes determined by the customs of Koto Dian Village, Hamparan Rawang District. This study uses a descriptive qualitative method where data is collected by observation, interviews and documentation studies. Data analysis used in this study is ethnographic analysis from Clifford Geertz, data hermeneutics, interpreting data, and interpretatively represented. The results of this study reveal that the Ngalu Kemenakan Tradition contains values ​​of brotherhood and solidarity, social values ​​and mutual cooperation values. The Ngalu Kemenakan tradition still exists and is carried out by the people of Koto Dian Village because it has a symbolic meaning for the community. The meaning of the symbol of money for welfare, the meaning of the symbol of the first child in the form of the datiu's appreciation for his brother's first child after he was married and the meaning of the symbol of the roll of money wrapped around the datiu who gathers with friendship bonds. For the meaning of activity in the Ngalu Nephew Tradition, it can be seen in the activity of draping a necklace of money around the nephew's neck showing togetherness and family cohesiveness, eating together as a form of family gratitude during the Ngalu Nephew tradition and reading prayers as the closing of the series of events and thanks to God Almighty.